2020
DOI: 10.1111/jne.12884
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity of the tuberoinfundibular dopaminergic neurones in the rat during the oestrous cycle and lactation

Abstract: The hypothalamic tuberoinfundibular dopaminergic (TIDA) neurones are critical with respect to regulating prolactin secretion from the anterior pituitary. Under most physiological conditions, they are stimulated by prolactin to release dopamine into the median eminence which subsequently suppresses further prolactin secretion from the lactotrophs. During lactation, the TIDA neurones are known to undergo both electrophysiological and neurochemical changes that alleviate this negativefeedback, thus allowing circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Z‐stack images were taken at 1‐μm steps through the ARC (1 AU pinhole). Close apposition of DBH‐ir fiber on kisspeptin soma or proximal dendrites was defined by the absence of black pixels between the two stained structures in at least two consecutive Z‐planes 32 . The proportion of kisspeptin‐ir neurons with at least one apposition was calculated for the ARC of OVX rats (3 fields/rat; n = 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Z‐stack images were taken at 1‐μm steps through the ARC (1 AU pinhole). Close apposition of DBH‐ir fiber on kisspeptin soma or proximal dendrites was defined by the absence of black pixels between the two stained structures in at least two consecutive Z‐planes 32 . The proportion of kisspeptin‐ir neurons with at least one apposition was calculated for the ARC of OVX rats (3 fields/rat; n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…Close apposition of DBH-ir fiber on kisspeptin soma or proximal dendrites was defined by the absence of black pixels between the two stained structures in at least two consecutive Z-planes. 32 The proportion of kisspeptin-ir neurons with at least one apposition was calculated for the ARC of OVX rats (3 fields/ rat; n = 3). To maximize the number of neurons evaluated, the fields analyzed were selected based on the highest density of kisspeptin-ir neurons.…”
Section: Immunohistochemistry and Confocal Microscopymentioning
confidence: 99%
“…Previous and most current reports suggested that neurochemical [8, 15], electrophysiological [16], and morphological [17] changes are present in TIDA neurons which allow the maintenance of elevated PRL levels during lactation. These effects seem to be downstream of the PRL-R, because its expression in dopamine neurons was demonstrated in lactating rats [18].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported here provide insights into the plasticity of TIDA neurones that may underlie their altered function during lactation. Yip et al 6 elegantly demonstrate a change in somatic spine density that would be expected to result in increased TIDA neurone excitatory output; it is possible that this supports the release of a TIDA neurone neuropeptide, such as met‐enkephalin that has been shown to be produced in these neurones in lactation, 7 which would stimulate prolactin release in a feed‐forward loop. This possibility is supported in the study by Silva et al 8 in this special issue, who show that reduced dopamine alone does not account for suckling induced rises in prolactin, indicative of a role for a prolactin‐releasing factor, such as met‐enkephalin.…”
mentioning
confidence: 97%
“…5 Two studies reported here provide insights into the plasticity of TIDA neurones that may underlie their altered function during lactation. Yip et al 6 elegantly demonstrate a change in somatic spine density that would be expected to result in increased TIDA neurone excitatory output; it is possible that this supports the release of a TIDA neurone neuropeptide, such as met-enkephalin that has been shown to be produced in these neurones in lactation, 7 The diversity of papers presented in this special issue and the novelty of many findings illustrate that investigation of the prolactin 2 of 2 | EDITORIAL and GH systems is not merely a matter of refining the understanding of a well-described system. Exciting advances in all aspects of both hormones are currently being made and will continue for the foreseeable future, from regulation by the brain and periphery, to temporal and differential effects on tissues that are only beginning to be understood.…”
mentioning
confidence: 99%